Prevention of invasive fungal infections in immunocompromised patients: the role of delayed-release posaconazole - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2015)
Posaconazole is a triazole antifungal agent that has broad-spectrum activity against many yeasts and filamentous fungi, including Candida species, Cryptococcus neoformans, Aspergillus species, and Zygomycetes. This drug has been approved for the prevention of invasive fungal infections in patients with neutropenia and for the treatment of invasive fungal infections in hematopoietic stem cell transplant recipients with graft-versus-host disease. Studies on the clinical efficacy, safety, tolerability, and cost-effectiveness of posaconazole therapy were performed using the oral suspension form of the drug. Pharmacokinetic studies have found that the oral suspension form of posaconazole has problemeatic bioavailability: its absorption is affected by concomitant medication and food. This article discusses the pharmacokinetic properties of the newly developed posaconazole delayed-release tablet formulation and reviews the efficacy, safety, and cost-effectiveness of both the oral suspension and the new tablet formulation. In conclusion, the posaconazole tablet formulation has better systemic bioavailability, thereby enabling once-daily administration and better absorption in the presence of concomitant medication and food. However, well-designed clinical studies are needed to evaluate the use of the tablet formulation in real-life settings.
Keywords: posaconazole delayed-release tablet; prophylaxis; invasive fungal infections; ORAL ANTIFUNGAL PROPHYLAXIS; ACUTE MYELOGENOUS LEUKEMIA; RISK NEUTROPENIC PATIENTS; STANDARD AZOLE THERAPY; ACUTE MYELOID-LEUKEMIA; IN-VITRO ACTIVITIES; PEDIATRIC-PATIENTS; COST-EFFECTIVENESS; ECONOMIC-EVALUATION; AMPHOTERICIN-B